기관지폐포세척술: 검사와 해설 - 이대근; Daegeun Lee; 허진영; Jin-young Huh (The Korean journal of medicine, 2024)
Bronchoalveolar lavage (BAL) is performed via bronchoscopy, typically under conscious sedation. It plays a crucial role in the differential diagnosis of lung disease, because it provides valuable information about the lung parenchyma, including cellular composition, the presence of microorganisms, and cytological features. Furthermore, BAL has therapeutic applications and is widely used in medical research. However, careful patient selection is required, because the diagnostic yield may vary and the procedure has inherent risks. (Korean J Med 2024;99:303-307)